La mirada mental de niños autistas que asisten a escuelas públicas de la ciudad de Temuco en Chile - Claudia Huaiquián Billeke; Juan Mansilla Sepúlveda (Ricerche di Pedagogia e Didattica, 2011)
This investigation consists of the evaluation of a program of intervention psicoeducativo based on images, applied to nine children with Widespread Disorder of the Development (TGD) of autistic type, which ages were fluctuating between 3 and 8 years of age that they were present at Temuco's city. The program focused to activate the development of the dimensions of anticipation and flexibility in children with TGD. For this, it was applied to them the Inventory of Development of Autistic Spectrum IDAS. Once executed the program they were evaluated again by the same instrument, significant differences being demonstrated in the dimensions of anticipation t = 0,039 (P <0.05); in addition results notexpected were found, in the scale of disorder of social development t = 0,040 (P <0.05). There were no significant evidences in the dimension of sense of own activity, a result being obtained of t = 0, 57 (P> 0, 05). The results reflect the efficiency of the application of the program of intervention with images which intention was to reach to the systematizing of the work with children and girls who suffer some widespread disorder of the development.